European Muslim, Radicalism, Terrorism, and Democracy: A Reflection - Alfian Alfian; Herdi Sahrasad; Dedy Tabrani; Al Chaidar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This article argues that, in the future, Europe Union (EU) is predicted to continue to confront the expression of Islamization of acts of terror and radicalism by Muslim youth amid the complexity of the problem and amid the fact that government security forces in Belgium and other European countries are often uncomplicated, low-paid secret agents, open to the movement of fundamentalism, and the proliferation of the black market of weapons. All this has made Europe a very vulnerable area against terrorist attacks and militarism in cloak of religion. Indeed, a problem and a challenge to be solved amid issues of potential cracking or collapse of the Europe Union.